Unfair advantage : the power of financial education: what schools will never teach you about money - Kiyosaki, Robert T. , 1947- (Plata Publishing, 2011)
True financial education is the path to creating the life you want for yourself and your family. Kiyosaki challenges people to change the one thing that is within your control : yourself. He demonstrates how real financial education gives you an unfair advantage, and delivers measurable results